2003
DOI: 10.1051/animres:2003037
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of repeated transport in pregnant goats and their offspring

Abstract: -Although pregnant farm animals can encounter different stressors on numerous occasions, studies on the physiological effects of repeated stress during gestation on females and their offspring are quite recent and still scarce. The present experiment was performed to study the effects of repeated transportations on some physiological parameters in pregnant goats and to determine whether repeated exposure to prenatal stress resulted in alterations in the hypothalamic-pituitaryadrenocortical (HPA) axis and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
6
2
1
Order By: Relevance
“…Higher ambient temperatures are known to increase both the amount of BW loss and shrink of transported animals (Coffey et al, 2001). Whereas other studies observed increased NEFA concentrations following TRANS (Duvaux-Ponter et al, 2003;Earley et al, 2010), the NEFA concentrations in the current study remained relatively stable. This may be due to the longer duration of TRANS utilized by Earley et al (2010) and the isolation from conspecifics in the goats used by Duvaux-Ponter et al (2003).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Higher ambient temperatures are known to increase both the amount of BW loss and shrink of transported animals (Coffey et al, 2001). Whereas other studies observed increased NEFA concentrations following TRANS (Duvaux-Ponter et al, 2003;Earley et al, 2010), the NEFA concentrations in the current study remained relatively stable. This may be due to the longer duration of TRANS utilized by Earley et al (2010) and the isolation from conspecifics in the goats used by Duvaux-Ponter et al (2003).…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast, when pregnant goats were repeatedly transported they failed to habituate (Duvaux-Ponter et al, 2003). This may have been due to their isolation from conspecifics during transportation, as isolation is an additional stressor (Duvaux-Ponter et al, 2003). However, the current data demonstrate temperament inhibits the ability of cattle to habituate to a transportation stressor.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Transport in isolation from other goats induced large increases in cortisol, glucose and non-esterified fatty acids (Duvaux-Ponter et al, 2003;Kannan et al, 2002). There was a greater elevation of cortisol concentrations when goats were not able to maintain visual contact with other animals and the longer they remained in isolation, the greater the emotional stress (Richardson, 2002).…”
Section: Separation During Transportmentioning
confidence: 99%
“…Goats are very gregarious, prefer to stay close together, and individuals are rarely seen apart from the group (Ross and Berg, 1956). Transport in isolation from other goats induced large increases in cortisol, glucose and non-esterified fatty acids (Duvaux-Ponter et al, 2003;Kannan et al, 2002).…”
Section: Separation During Transportmentioning
confidence: 99%